Organizational Self-Perception and Environmental Image Measurement - Leister, Douglas V.; MacLachlan, Douglas L. (Academy of Management Journal, 1975)
Relative perceptions of higher educational institutions in western Washington state are reported with respect to organizational self-perception and environmental image. In addition, organizational and managerial implications inherent in the relative perceptions are drawn. The research methodology employed is multidimensional scaling and multidimensional unfolding.